Economics of monetary union - Grauwe, Paul de. (Oxford ; New York : Oxford University Press, 2007)
EMU as a classic text analyzes the costs and benefits associated with having one currency as well as the practical workings and current issues involved with the euro. In the first part, the author considers the implications of joining a monetary union through an economic cost & benefit analysis. The second part looks at the reality of monetary unions by analyzing Europe's experience, how it was designed to conduct a single monetary policy.
The costs of a common currency -- The theory of optimum currency areas : a critique -- The benefits of a common currency -- Costs and benefits compared -- Monetary and political union -- The fragility of incomplete monetary unions -- The transition to a monetary union -- The European Central Bank -- Monetary policy in the eurozone -- Fiscal policies in monetary unions -- The euro and financial markets.
Includes bibliographical references and index.
nmn 10/05/13
Loans
Keywords: European Monetary System (Organization); Monetary unions -- European Union countries; Monetary policy -- European Union countries